CLT – versatile, fast and ecological construction material - Vatanen, Mikko; Ahoranta, Tytti; Sirkka, Antti; Pirttinen, Valtteri (Lapin ammattikorkeakoulu, 2017)
This collection of articles examines CLT as a construction material and its characteristics from the perspectives of worksite operations and the design process, along with exploring the related environmental effects. The articles also present Finnish CLT operators and reference projects. Finnish CLT oper-ators and reference projects have been collected at the end of the work. This knowledge base is intended for distribution to all construction field operators who are interested in the possibilities of CLT as a construction material. Studies related to CLT construction have also been previously conducted under a joint project between Digipolis Oy, Vocational College Lappia and Lapland University of Applied Sciences. Visits to production facilities, par-ticipation in domestic and foreign seminars and conferences, and study of written and visual material on CLT construction have also contributed to the process and provided additional information on solid wood element construc-tion, which is rapidly gaining ground on global scale. The “CLT – versatile, fast and ecological construction material” collection of articles was authored and compiled under the Fugure possibilities for CLT project. The Future possibilities for CLT (FCLT) is implemented as a ERDF-funded Interreg Nord research project involving the Luleå University of Tech-nology, Technical Research Institute of Sweden (SP), Centria UAS, Digipolis Oy and Lapland UAS. The project was initiated in September 2015 and will continue until October 2018. The primary objective is to promote the diverse use of CLT and increase awareness of the possibilities provided by CLT con-struction in the Interreg Nord region.